Pre-processing Cooling of Harvested Grapes Induces Changes in Berry Composition and Metabolism, and Affects Quality and Aroma Traits of the Resulting Wine - Margherita Modesti (Frontiers Media S.A., 2021)
Due to the greenhouse gas increase, grapes are often exposed to high temperatures in several growing areas especially during the final developmental stages, and this is particularly true when early ripening cultivars are harvested. This may cause undesirable effects on berry metabolism and composition and wine quality, particularly concerning the aroma profile. Harvesting at night or keeping the harvested grapes in cold rooms before vinification are empirical protocols applied in specific viticultural areas. To study the effects of decreasing berry temperature after harvest, white-skinned berries (cv Vermentino) were maintained at 4 or 10°C for 24 or 48 h before processing (pre-cooling). Control grapes were kept at 22°C. Grapes cooled at 10°C for 24 and 48 h resulted richer in polyphenols and showed a significant up-regulation of genes involved in polyphenols biosynthesis (i.e., VvPAL, VvSTS2, and VvFLS1). Similar behavior was observed in samples kept at 4°C for 48 h. Pre-cooling induced specific changes in the volatile organic compound (VOC) profiles. In particular, higher amounts of a specific subcategory of terpenes, namely sesquiterpenes, were detected in cooled samples. The induction of the expression of key genes involved in terpenoids biosynthesis (VvHDR, VvDX3, VvTER, VvGT14) was detected in cooled grapes, with variable effects depending on temperature and treatment duration. In both cooled samples, the evolution of alcoholic fermentation followed a regular trend but ended earlier. Higher phenolic content was detected in wines obtained from the 10°C-treated grapes. Higher residual concentration of malic acid at the end of fermentation was detected in wine samples from grapes pre-cooled at 4°C. Sesquiterpenes also showed a general increase in wines from cooled grapes, especially after pre-cooling at 10°C for 48 h. Different sensory profiles characterized the wine samples, with the best scores in terms of general pleasantness obtained by the wine produced from grapes pre-cooled at 4°C for 24 h. These results demonstrate that pre-cooling harvested grapes induces specific effect on the VOC profile and other quality parameters of Vermentino wine, and this appears to be the result of specific metabolic and compositional changes occurring in the berries.